1985
DOI: 10.1159/000183518
|View full text |Cite
|
Sign up to set email alerts
|

Apoprotein A-I and High Density Lipoprotein Subtractions in Patients with Chronic Renal Failure Receiving Hemodialysis

Abstract: Serum concentration of apoprotein A-I (apo A-I) and cholesterol content in high density lipoprotein (HDL) subfractions have been studied in 19 men and 11 women at the end stage of chronic renal failure undergoing hemodialysis. HDL2 cholesterol concentration was decreased in males [0.33 ± 0.12 (mean ± SD) mmol/l, controls 0.45 ± 0.09 mmol/l; p < 0.001]; in females HDL2 cholesterol was also decreased although without statistical significance (0.45 ± 0.15 vs. 0.55 ± 0.10 mmol/l). HDL3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The pattern o f hyperlipoproteinemia in patients with nephrotic syndrome is not completely understood and con flicting results have been described [8][9][10][11][12][16][17][18][19]. To explain this disagreement, several possibilities arise but the most probable is the misleading effect of frequently concomitant complications such as renal failure and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pattern o f hyperlipoproteinemia in patients with nephrotic syndrome is not completely understood and con flicting results have been described [8][9][10][11][12][16][17][18][19]. To explain this disagreement, several possibilities arise but the most probable is the misleading effect of frequently concomitant complications such as renal failure and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In our uremic patients, the lipid distribution o f H D L was significantly different from that observed in the other nephrotic patients with significantly lower H D L cholesterol values. This is the more controver sial aspect o f the pattern of hyperlipidemia in the nephrotic syndrome, and different authors have reported high, low and normal H D L cholesterol values [16][17][18][19]. High levels have been interpreted as the result o f high serum lipopro tein (a) levels in the nephrotic syndrome contaminating the H D L samples when cholesterol is assayed [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our experi ence glucose intolerance is still present in over 50% of the patients on RDT [57], mainly in patients who had started dialysis with very low residual renal function and fol lowing long-lasting treatment with low-pro tein diet [70], Hyperdyslipidemia Some 70% of patients with chronic renal failure exhibit abnormalities of the lipid pat tern [71][72][73][74] which are not modified at all by RDT [75,76]. The phenotypic features of uremic (or dialysis) hyperlipidemia include high total triglyceride and normal or low to normal total cholesterol and lower HDL cho lesterol levels, a corresponding increase in very-low-density lipoproteins and interme diate-density lipoproteins with a decrease in high-density lipoproteins, and, finally, changes of both lipid and apoprotein compo sition of lipoprotein particles [77,78].…”
Section: Glucose Intolerancementioning
confidence: 99%
“…During recent years, with increasing knowledge and information gained from a number of studies, it becomes clear that the predominant change in lipoprotein is qualitative rather than quantitative [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%